Comparison Between Conventional and Microwave Methods For Extraction Pectin and Degree of Esterification from Orange (Citrus sinesis) and Grapefruit (Citrus paradisi) Peels (Baghdad Science Journal, 2016)
In this study Microwave and conventional methods have been used to extract and estimate pectin and its degree of esterification from dried grapefruit and orange peels. Acidified solution water with nitric acid in pH (1.5) was used. In conventional method, different temperature degrees for extraction pectin from grape fruit and orange(85 ,90 , 95 and 100?C) for 1 h were used The results showed grapefruit peels contained 12.82, 17.05, 18.47, 15.89% respectively, while the corresponding values were 5.96, 6.74, 7.41 and 8.00 %, respectively in orange peels. In microwave method, times were 90, 100, 110 and 120 seconds. Grapefruit peels contain 13.86, 16.57, 18.69, and 17.87%, respectively, while the corresponding values were of 6.53, 6.68, 7.28 and 9.05 %, respectively in orange peels. The degree of esterification increased gradually in both methods. The maximum values were of 69.7% in orange and of 67% in grapefruit at 95 °C in conventional method, while microwave method the values gave 68.8% and 66.6% for orange and grape fruit pectin at 110 sec, respectively .